Tissue sodium concentration within white matter correlates with the extent of small vessel disease - Adlung, Anne; Samartzi, Melina; Schad, Lothar R.; Neumaier-Probst, Eva; Fatar, Marc; Mohamed, Sherif A. (Cerebrovascular diseases, 2021)
Introduction: Sodium MRI (23Na MRI) derived biomarkers such as tissue sodium concentration (TSC) provide valuable information on cell function and brain tissue viability and has become a reliable tool for the assessment of brain tumors and ischemic stroke beyond pathoanatomical morphology. Patients with major stroke often suffer from different degrees of underlying white matter lesions (WMLs) attributed to chronic small vessel disease. This study aimed to evaluate the WM TSC in patients with an acute ischemic stroke and to correlate the TSC with the extent of small vessel disease. Furthermore, the reliability of relative TSC (rTSC) compared to absolute TSC in these patients was analyzed. Methodology: We prospectively examined 62 patients with acute ischemic stroke (73 ± 13 years) between November 2016 and August 2019 from which 18 patients were excluded and thus 44 patients were evaluated. A 3D 23Na MRI was acquired in addition to a T2-TIRM and a diffusion-weighted image. Coregistration and segmentation were performed with SPM 12 based on the T2-TIRM image. The extension of WM T2 hyperintense lesions in each patient was classified using the Fazekas scale of WMLs. The absolute TSC in the WM region was correlated to the Fazekas grades. The stroke region was manually segmented on the coregistered absolute diffusion coefficient image and absolute, and rTSC was calculated in the stroke region and compared to nonischemic WM region. Statistical significance was evaluated using the Student t-test. Results: For patients with Fazekas grade I (n = 25, age: 68.5 ± 15.1 years), mean TSC in WM was 55.57 ± 7.43 mM, and it was not statistically significant different from patients with Fazekas grade II (n = 7, age: 77.9 ± 6.4 years) with a mean TSC in WM of 53.9 ± 6.4 mM, p = 0.58. For patients with Fazekas grade III (n = 9, age: 81.4 ± 7.9 years), mean TSC in WM was 68.7 ± 10.5 mM, which is statistically significantly higher than the TSC in patients with Fazekas grade I and II (p < 0.001 and p = 0.05, respectively). There was a positive correlation between the TSC in WM and the Fazekas grade with r = 0.48 p < 0.001. The rTSC in the stroke region was statistically significant difference between low (0 and I) and high (2 and 3) Fazekas grades (p = 0.0353) whereas there was no statistically significant difference in absolute TSC in the stroke region between low (0 and I) and high (2 and 3) Fazekas grades. Conclusion: The significant difference in absolute TSC in WM in patients with severe small vessel disease; Fazekas grade 3 can lead to inaccuracies using rTSC quantification for evaluation of acute ischemic stroke using 23 Na MRI. The study, therefore, emphasizes the importance of absolute tissue sodium quantification.
Published online: March 17, 2021
Gesehen am 24.11.2022